Self-evaluation of the modern languages major focused in two factors: students and resources at the foreign languages department, University of El Salvador, 2012 - Pineda Campos, Elba Beatriz; Ayala Bran, Francisco José; Flores Polanco, Julio César; Cruz Cubías, Juan Carlos; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2012)
The evaluation of the Modern Languages Major is focused on two main aspects, “Students and Resources”, whose purpose is to determine the existence of academic quality standards and/or minimum quality features in the aspects above mentioned. To perform this evaluation the program evaluation guidelines published by CSUCA and SICEVAES were used. This document provides guidance to Central American Universities toward planning and implementing evaluation processes aiming at improving their different academic programs.
Anexos: instrumentos de la investigación.
Tesis -- (Licenciatura en Lenguas Modernas especialidad Francés e Inglés) -- Universidad de El Salvador, San Salvador, 2012
Bibliografía : hojas 117-118
Audiencia general
La tesis está en formato digital.
Texto en inglés
Keywords: Educación superior; Evaluación institucional